2009
DOI: 10.2298/vsp0908671d
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal dysphagia as dominant and life-threatening symptom in dermatomyositis

Abstract: In cases of dermatomyositis with the serious dysphagia, percutaneous endoscopic gastrostomy should be performed as soon as possible. Overall survival rate is low, even with an adequate therapy administration. Inflammatory myopathies should be considered in any patient with oropharyngeal dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
2
1
1
Order By: Relevance
“…In contrast, a less strict criterion of refractoriness was observed in previous studies and data on severe symptoms such as dysphagia were not reported hampering comparison with the present [4][5][6][7][8][9][10][11]. In fact, among patients evaluated in the present study, more than two-thirds had dysphagia, a known serious problem in patients with IIM that can be associated with nutritional deficiency, aspiration pneumonia and poor prognosis [18]. The rituximab protocol was a more aggressive approach than others previously reported [4][5][6][7][8][9][10][11], and included pre-infusion of methylprednisolone and intravenous human immunoglobulin for the majority of the patients.…”
Section: Discussioncontrasting
confidence: 73%
“…In contrast, a less strict criterion of refractoriness was observed in previous studies and data on severe symptoms such as dysphagia were not reported hampering comparison with the present [4][5][6][7][8][9][10][11]. In fact, among patients evaluated in the present study, more than two-thirds had dysphagia, a known serious problem in patients with IIM that can be associated with nutritional deficiency, aspiration pneumonia and poor prognosis [18]. The rituximab protocol was a more aggressive approach than others previously reported [4][5][6][7][8][9][10][11], and included pre-infusion of methylprednisolone and intravenous human immunoglobulin for the majority of the patients.…”
Section: Discussioncontrasting
confidence: 73%
“…IIM can result in impairment of the oral [ 29 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], pharyngeal [ 7 , 23 , 24 , 27 , 29 , 31 , 32 , 33 , 44 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ,…”
Section: Resultsunclassified
“…Reduced pharyngeal contractility can result in insufficient pharyngeal bolus clearance [ 139 ]. Consequently, myositis patients often show pharyngeal residue after swallowing [ 7 , 27 , 29 , 31 , 33 , 44 , 58 , 59 , 60 , 61 , 65 , 66 , 67 , 69 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 83 , 84 , 86 , 87 , 91 , 93 , 96 , 100 , 101 , 103 , 104 , 106 , 111 , 112 , 115 ]. These can impact on swallowing safety and ultimately cause aspiration, which is a frequently reported finding [ 33 , 78 , 81 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation